(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the effectiveness of using videos in teaching English to preschool children. It highlights the benefits of incorporating videos as a supplementary tool in early childhood language learning. Through visual and auditory stimuli, videos help young learners engage with new vocabulary, pronunciation, and sentence structures. The article discusses various methods of integrating videos into the classroom, presents results from studies on video use, and offers a discussion on how videos can support language development in preschoolers. Finally, it concludes by emphasizing the value of videos in creating an interactive and dynamic learning environment for young learners.